2015
DOI: 10.1016/j.expneurol.2015.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial influences of paclitaxel and strain on axonal transport

Abstract: Paclitaxel is an effective chemotherapeutic agent that, despite its common use, often causes peripheral sensory neuropathy. In neurons, paclitaxel binds to and stabilizes microtubules, and through unknown mechanisms, bundles microtubules and disrupts their organization. Because microtubules serve as tracks on which a variety of axonal cargoes are transported, a leading hypothesis for the etiology of paclitaxel-induced neuropathy is that these changes to microtubule organization impair axonal transport. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Studies using lower paclitaxel concentrations have also observed bulk transport decreases (21, 22, 48) and mitochondrial transport decreases (20, 49), however these studies were not carried out on adult mammalian DRG neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using lower paclitaxel concentrations have also observed bulk transport decreases (21, 22, 48) and mitochondrial transport decreases (20, 49), however these studies were not carried out on adult mammalian DRG neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Varied hypotheses have been proposed, including: compromised transport of proteins and organelles (Shprung and Gozes, 2009, Shemesh and Spira, 2010, LaPointe et al, 2013), changes in receptor and channel localization and function (Flatters and Bennett, 2004, Matsumoto et al, 2006, Xiao et al, 2007, Nieto et al, 2008, Chen et al, 2011, Okubo et al, 2011, Kawakami et al, 2012, Hara et al, 2013, Chen et al, 2014) and/or activation of an immune response (Siau et al, 2006, Peters et al, 2007, Pevida et al, 2013, Warwick and Hanani, 2013, Zhang et al, 2013, Li et al, 2014, Li et al, 2015). Stabilization of microtubules can alter both anterograde and retrograde axonal transport of mitochondria along the microtubules (Nennesmo and Reinholt, 1988, Morris and Hollenbeck, 1995, Nakata and Yorifuji, 1999, Theiss and Meller, 2000, Shemesh and Spira, 2010, Bober et al, 2015). Alterations in mitochondrial trafficking could subsequently alter neuronal sensitivity via increased reactive oxygen and nitrogen species production (Kim et al, 2010, Fidanboylu et al, 2011, Barriere et al, 2012, Doyle et al, 2012, Janes et al, 2013), changes in calcium buffering, and local changes in energy production within the nerve terminals (Abou-Sleiman et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Though this idea is currently highly speculative, altered nerve mechanics may thus influence neuropathic progression. Such damage may impact cell function directly, due to microtubule breakage, such as that observed in neurons loaded at high strain rates (Tang-Schomer et al,2012), or indirectly, by amplifying axonal transport defects (Bober et al,2015) . Given the possibility of a mechanical contribution to neuropathy, the physical management of patients treated with paclitaxel, including the development of effective post- Scale bar = 5mm.…”
Section: Discussionmentioning
confidence: 99%